PENGENALAN APLIKASI QRIS SEBAGAI ALAT PEMBAYARAN NON TUNAI UNTUK MEMPERMUDAH TRANSAKSI BAGI PELAKU USAHA TOKO KELONTONG DI DISTRIK SENTANI KABUPATEN JAYAPURA. - Misfah Muslimawati (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2024)
Today's development of digital technology has spread to all aspects that have led to a change in people's behaviour from conventional to digital. It has also affected conventional that are beginning to grow into e-business, such developments not only have undergone a shift in terms of management systems, but have later shifted to online-based payment systems that are considered accountable, practical and secure. The majority of people today use gadgets in transactions both online and offline because they are considered more efficient so that most stores and shopping centers provide QR-Code-based digital payment alternatives. However, not many UMKM are using QRIS as a payment alternative, so it is necessary to have an introduction and understanding of the importance of using QRIs as a digital payment tool other than cash payment. In addition, training is needed to improve the ability of UMKM perpetrators in applying QRIS, as part of digitalization, thus opening up opportunities to grow in line with the changing behaviour of deadly transaction that is increasingly open to adopting digital payments.